Uma metodologia de avaliação do design de interfaces baseado no estudo de caso do sistema Universidade Aberta do Brasil UAB/UFAL - Ivo, Jose Kleber (2011)
This study presents an evaluation model able to detect usability problems in Virtual Learning Environments. This study was developed through the context of the Open University System of Brazil, Federal University of Alagoas (UFAL). It’s principle evaluate the Moodle interface, identifying potential usability problems. Errors were detected on the interface, will be appointed the usability criterion that need to be improved. Dimensions measured in the model are easy to learn, efficient, easy to remember, have few errors and create satisfaction. In this sense, it were used the original list and revised version of the heuristics by Jakob Nielsen sealer as part of study of case. The methodology used in the evaluation model finds support in Preece, et al. (2007, p. 24-55, 339-357), evaluation D E C I D E model. Graphic was constructed using results of evaluations and analysis carried out by observing each criterion of usability. The evaluation model suggests qualitative metrics. The case study's Evaluation of Moodle Platform involved 10 evaluators. The Virtual Learning Environment received a total of 20 criterion evaluated; 13 criterion approved according to the analysis, and seven criterion evaluators that need to be improved. In the general analysis, it was observed that the Moodle environment has a good level of usability, but some of the aspects assessed showed inadequate and need to be improved for a better interaction between user and interface.